REPRESENTAÇÕES DA IMIGRAÇÃO UCRANIANA NAS POESIAS DE HELENA KOLODY - Boruch, Tiago (2018)
This dissertation has as objective to analyze Helena Kolody poems and her representations around Ukraine immigration in Paraná. From the dialogue of history with the literature we aim to understand how her creative project is consecrated by the critique, becoming a reference to discuss about paranaense identity. For this, we seek to evidence the intellectual position of Kolody in the paranaense artistic field as well as analyze from her poetic construction the regional characteristics imprinted around the Ukraine immigration. We seek to show the poetic production of author as spokesperson of slavs realizing it as a manner of contact and of analyze of author life history with a sensitive understanding of her Slavic roots. Inserted in the New Cultural History field, we intend to give emphasis to the feelings and emotions built around immigrant people, considered one of more important elements of identity of paranaense. We believe that Kolody’s consecration happened because she incorporated official symbolic elements, in special, of Paranista movement, collaborating in the construction of a unique history that focuses the ideal immigrant, her saga and victory. Then we walk the paths discussing about identity, culture, and everyday Slavic life, focusing on the investigation of poems that refer to imaginaries of urban and rural space that played an important role on Ukraine immigrant identity.